Metallised Fuel rich Propellants for Solid Rocket Ramjet: A Review - Athawale, B. K.; Asthana, S. N.; Singh, Haridwar (Defence Science Journal, 2013)
This paper reviews the research work carried out in the field of metallised fuel-rich propellants (FRP). Limitations and merits of various potential metals (Al, Mg, B, Be, or Zr) as a component of FRP are discussed. The paper also includes a discussion on the combustion mechanism of metallised propellants, including problem areas and probable remedial measures. Zirconium and Ti appear to have potential to offer FRP with efficient combustion. Ideal performance is not achieved with current systems based on Al and B and further work is needed to develop FRP having all three desirable attributes, viz., ease of ignition, stable combustion and high specific impulse (I/sub sp/) in a single composition.